Native games indigenous peoples and sports in the post-colonial world - Hallinan, Chris; Judd, Barry (Research in the sociology of sport ;, 2013)
Research on Indigenous participation in sport offers many oppertunities to better understand the political issues of equality, empowerment, self-determination and protection of culture and identity. This volume compares and conceptualises the sociological significance of Indigenous sports in different international contexts. The contributions, all written by Indigenous scholars and those working directly in Indigenous/Native Studies units, provide unique studies of contemporary experiences of Indigenous sports participation. The papers investigate current understandings of Indigeneity found to circulate throughout sports, sports organisations and Indigenous communities. by (1): situating attitudes to racial and cultural difference within the broader sociological processes of post colonial Indigenous worlds (2): interrogating perceptions of Indigenous identity with reference to contemporary theories of identity drawn from Indigenous Studies and (3): providing insight to increased Indigenous participation, empowerment and personal development through sport with reference to sociological theory.